2006
DOI: 10.1210/en.2005-0895
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Regulates Cellular Glutathione Content via Modulation of γ-Glutamate-Cysteine Ligase Catalytic Subunit Expression

Abstract: Adrenomedullin (AM) participates in a wide range of physiological and pathological processes including vasorelaxation, angiogenesis, cancer promotion, and apoptosis. Recently, it has been reported that AM protects a variety of cells against oxidative stress induced by stressors such as hypoxia, ischemia/reperfusion, and hydrogen peroxide through the phosphatidylinositol 3-kinase (PI3K)-dependent pathway. However, the molecular mechanisms underlying the pathway of cell survival against hypoxic injury are largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…In consistent with our study, others' studies also indicated importance of the GC rich region to be necessary for transcriptional activity [Tomonari et al, 1997]. Although this study did not assessed the ARE and its binding factor Nrf1/2 which have been demonstrated in the induction of GCLC gene by a wide range of stimuli including quercetin [Myhrstad et al, 2002;Dickinson et al, 2003], it is unlikely that the only interaction of ARE sites with Nrf1/2 is sufficient to drive full activation of the gene promoter because GCLC promoter without ARE motifs still significantly responded to various stimuli [Kim et al, 2006b;Kimura et al, 2009]. In addition, cells deficient in Nrf1 or Nrf2 still retained ability to activate GCLC promoter by tert-butylhyroquinone [Yang et al, 2005].…”
Section: Discussionmentioning
confidence: 88%
“…In consistent with our study, others' studies also indicated importance of the GC rich region to be necessary for transcriptional activity [Tomonari et al, 1997]. Although this study did not assessed the ARE and its binding factor Nrf1/2 which have been demonstrated in the induction of GCLC gene by a wide range of stimuli including quercetin [Myhrstad et al, 2002;Dickinson et al, 2003], it is unlikely that the only interaction of ARE sites with Nrf1/2 is sufficient to drive full activation of the gene promoter because GCLC promoter without ARE motifs still significantly responded to various stimuli [Kim et al, 2006b;Kimura et al, 2009]. In addition, cells deficient in Nrf1 or Nrf2 still retained ability to activate GCLC promoter by tert-butylhyroquinone [Yang et al, 2005].…”
Section: Discussionmentioning
confidence: 88%
“…AM-deficient mice exhibiting a more severe organ injury in multiple systems that were caused by enhanced oxidative stress [15]. AM treatment can increase cellular glutathione levels via upregulation of gamma-glutamate-cysteine ligase (γ-GCL) catalytic subunit expression [16], and attenuate cardiac oxidative stress by inhibiting NADPH oxidase activity [17]. However, the effect of AM on pulmonary oxidative stress and inflammation that could occur during the development of hyperoxia-induced ALI has so far been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS level was greatly increased in the AM HT mice and the AM WT CCl4 group. Previous reports have shown that AM plays a role as an antioxidant in two ways: suppressing ROS production [1,3,8] and promoting the ROS scavenging system [10]. Consequently, the increased ROS might be due to the down-regulated AM.…”
Section: Discussionmentioning
confidence: 98%
“…GSH is a key regulator of cellular redox and is involved in the maintenance of interior cellular redox balance in mammals [10,23].…”
Section: Discussionmentioning
confidence: 99%